A study on the approaches of CLIP implemented NFPE school and regular NFPE school - Ahmed, Ameena (BRAC Research and Evaluation Division (RED), 2019)
A study on the approaches of CLIP implemented NFPE and regular NFPE schools was undertaken to find out the variations of teaching-learning situations in the classroom of these schools. In the study, detailed and thorough investigation was made to ascertain the effectiveness of teaching-learning process, to assess its strengths and weaknesses in the class-room situation and to observe various ways of communication between the teachers and learners. The study was conducted in four NFPE . schools (CLIP implemented and two regula), on a sample of 132 learners (1st year). The role of the teacher was found very prominent in the class room. The study clearly revealed that the learners of regular NFPE school were found better in 'reading' but not in 'writing' while those of CLIP implemented schools showed just the opposite result. In respect to learners' achievement tests, the results clearly showed some deficiencies. However, some specific recommendations had been made here with the hope that the NFPE programme would be benefited.